Functional nanonetwork-structured polymers and carbons with silver nanoparticle yolks for antibacterial application. Issue 70 (17th August 2017) - Lin, Yanhuan; Xiong, Kairong; Lu, Zhitao; Liu, Shaohong; Zhang, Zhaojie; Lu, Yuheng; Fu, Ruowen; Wu, Dingcai
Abstract : Functional nanonetwork-structured polymers and carbons with silver nanoparticle yolks were fabricated and demonstrated superior long-term antibacterial performances. Abstract : Functional nanonetwork-structured polymers and carbons with silver nanoparticle yolks (∼20 nm) were successfully fabricated via hypercrosslinking chemistry. Benefiting from the hierarchical porous nanonetwork structure and high surface areas (up to 566 m 2 g −1 ), the as-prepared nanocomposites demonstrated superior long-term antibacterial performances ( e.g., 6 days).